Safety in transportation: a review of the concept, its context, safety preservation and improvement effectiveness - Maciej SZCZUKOWSKI (Scientific Journal of Silesian University of Technology. Series Transport, 2017)
The article presents definitions of and approaches to the concept of safety in order to confirm the subjective character of its determination, description, and interpretation. By presenting examples of security statistics and safety-related behaviours, its ambiguity and complexity are revealed. The author draws attention to the media’s attitude towards safety-related incidents. With reference to contemporary scientific knowledge about the methods of improving safety in transportation organizations, the author also suggests that safety improvement initiatives should focus more strongly on facilitating closer cooperation between leaders, superiors and subordinates with different levels of experience.